Interaction of α(V)β(3) and α(V)β(6) Integrins with Human Parechovirus 1 - Seitsonen, Jani (American Society for Microbiology (ASM), 2010)
Human parechovirus (HPEV) infections are very common in early childhood and can be severe in neonates. It has been shown that integrins are important for cellular infectivity of HPEV1 through experiments using peptide blocking assays and function-blocking antibodies to α(V) integrins. The interaction of HPEV1 with α(V) integrins is presumably mediated by a C-terminal RGD motif in the capsid protein VP1. We characterized the binding of integrins α(V)β(3) and α(V)β(6) to HPEV1 by biochemical and structural studies. We showed that although HPEV1 bound efficiently to immobilized integrins, α(V)β(6) bound more efficiently than α(V)β(3) to immobilized HPEV1. Moreover, soluble α(V)β(6), but not α(V)β(3), blocked HPEV1 cellular infectivity, indicating that it is a high-affinity receptor for HPEV1. We also showed that HPEV1 binding to integrins in vitro could be partially blocked by RGD peptides. Using electron cryo-microscopy and image reconstruction, we showed that HPEV1 has the typical T=1 (pseudo T=3) organization of a picornavirus. Complexes of HPEV1 and integrins indicated that both integrin footprints reside between the 5-fold and 3-fold symmetry axes. This result does not match the RGD position predicted from the coxsackievirus A9 X-ray structure but is consistent with the predicted location of this motif in the shorter C terminus found in HPEV1. This first structural characterization of a parechovirus indicates that the differences in receptor binding are due to the amino acid differences in the integrins rather than to significantly different viral footprints.